2019
DOI: 10.1002/chem.201903949
|View full text |Cite
|
Sign up to set email alerts
|

Undiscovered Potential: Ge Catalysts for Lactide Polymerization

Abstract: Polylactide (PLA) is a high potential bioplastic that can replace oil‐based plastics in a number of applications. To date, in spite of its known toxicity, a tin catalyst is used on industrial scale which should be replaced by a benign catalyst in the long run. Germanium is known to be unharmful while having similar properties as tin. Only few germylene catalysts are known so far and none has shown the potential for industrial application. We herein present Ge complexes in combination with zinc and copper, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 95 publications
1
29
0
Order By: Relevance
“…The Ar CN *GeCl is also able to coordinate ZnCl 2 and CuX (X=Cl and I) to yield new heterobimetallic complexes {[Ar CN *(Cl)Ge]MX} 2 (M=ZnCl, Cu) (Scheme ) . The substitution reaction with K[BEt 3 H] provided {[Ar CN *(H)Ge]ZnCl 2 } 2 .…”
Section: Group 14 Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ar CN *GeCl is also able to coordinate ZnCl 2 and CuX (X=Cl and I) to yield new heterobimetallic complexes {[Ar CN *(Cl)Ge]MX} 2 (M=ZnCl, Cu) (Scheme ) . The substitution reaction with K[BEt 3 H] provided {[Ar CN *(H)Ge]ZnCl 2 } 2 .…”
Section: Group 14 Complexesmentioning
confidence: 99%
“…These complexes were tested as catalysts in the ring opening polymerization (ROP) of lactides (Scheme ). The polymerizations were done as solvent free experiments at 150 °C and complex {[Ar CN *(H)Ge]ZnCl 2 } 2 exhibited excellent activity with k p =3.806±0.315 L mol −1 s −1 which is much better than industrially used Sn(Oct) 2 with k p =(0.084±0.02) L mol −1 s −1 …”
Section: Group 14 Complexesmentioning
confidence: 99%
“…Recently, we have shown that the reaction of the N!Ge coordinated germylene L(Cl)Ge (L = 2-Et 2 NCH 2 -4,6-tBu 2 -C 6 H 2 ) with CuCl or (CuI) 4 (SMe 2 ) 3 yielded the monomeric complexes [L(Cl)Ge] 2 CuX (X = Cl, I). [10] As substitution reactions of [L(Cl)Ge] 2 CuCl provided mixture of products and no selectivity was observed, here we present the reactivity of the [L(Cl)Ge] 2 CuI (1), where two L(Cl)Ge fragments coordinate monomeric CuI (Scheme 1). [10] The presence of two different halides in 1 allowed us to study its selective substitution reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[10] As substitution reactions of [L(Cl)Ge] 2 CuCl provided mixture of products and no selectivity was observed, here we present the reactivity of the [L(Cl)Ge] 2 CuI (1), where two L(Cl)Ge fragments coordinate monomeric CuI (Scheme 1). [10] The presence of two different halides in 1 allowed us to study its selective substitution reactions.…”
Section: Introductionmentioning
confidence: 99%
“…With TOF values of up to 100000 h −1 the catalyst is classified as extremely active under industrial conditions. In addition to this development of zinc complexes for the ROP of technical grade lactide, a non‐toxic germanium complex ( 5 ) has recently been synthesized, which proved to be active in ring‐opening polymerization . Kinetic investigations showed that the germanium atom is the active center of the polymerization and that a CIM mechanism is proceeding.…”
Section: Introductionmentioning
confidence: 99%